Amide proton transfer imaging for differentiation of tuberculomas from high-grade gliomas: Preliminary experience. Issue 5 (October 2021) - Kulanthaivelu, Karthik; Jabeen, Shumyla; Saini, Jitender; Raju, Sanita; Nalini, Atchayaram; Sadashiva, Nishanth; Hegde, Shashank; Rolla, Narayana Krishna; Saha, Indrajit; M, Netravathi; Vengalil, Seena; Swaroop, Saikrishna; et al.
Purpose: Tuberculomas can occasionally masquerade as high-grade gliomas (HGG). Evidence from magnetisation transfer (MT) imaging suggests that there is lower protein content in the tuberculoma microenvironment. Building on the principles of chemical exchange saturation transfer and MT, amide proton transfer (APT) imaging generates tissue contrast as a function of the mobile amide protons in tissue's native peptides and intracellular proteins. This study aimed to further the understanding of tuberculomas using APT and to compare it with HGG. Method: Twenty-two patients ( n  = 8 tuberculoma; n  = 14 HGG) were included in the study. APT was a 3D turbo spin-echo Dixon sequence with inbuilt B0 correction. A two-second, 2 μT saturation pulse alternating over transmit channels was applied at ±3.5 ppm around water resonance. The APT-weighted image (APTw) was computed as the MT ratio asymmetry (MTRasym ) at 3.5 ppm. Mean MTRasym values in regions of interest (areas = 9 mm 2 ; positioned in component with homogeneous enhancement/least apparent diffusion coefficient) were used for the analysis. Results: MTRasym values of tuberculomas ( n  = 14; 8 cases) ranged from 1.34% to 3.11% ( M  = 2.32 ± 0.50). HGG ( n  = 17;14 cases) showed MTRasym ranging from 2.40% to 5.70% ( M  = 4.32 ± 0.84). The inter-group difference in MTRasym was statistically significant ( p  < 0.001). APTw images in tuberculomas were notable for high MTRasym values in the perilesional oedematous-appearing parenchyma (compared to contralateral white matter; p  < 0.001). Conclusion: Tuberculomas demonstrate lower MTRasym ratios compared to HGG, reflective of a relative paucity of mobile amide protons in the ambient microenvironment. Elevated MTRasym values in perilesional parenchyma in tuberculomas are a unique observation that may be a clue to the inflammatory milieu.